The Development of Mobile Learning (M-Learning) Apps Adik-Adik Solat to Enhance Learning Experience in Solat: Pembangunan Aplikasi Pembelajaran Mudah Alih (M-Learning) Adik-Adik Solat untuk Meningkatkan Pengalaman Pembelajaran dalam Solat - Mohamed Ali, Mohd Hatta; Hafidzi, Anwar; Mohd Herrow, Mohd Firdaus; Yahya, Mokhtar; Ismail, Affero; Abdul Samad, Noorazman (Journal of Quranic Sciences and Research, 2022)
Prayer (Solat) is an act of worship that is a pillar of Islam. It is an obligation for a Muslim that must be performed. Many verses of the Qur'an and hadith emphasize the importance of educating prayer from an early age. The learning of prayer is learned starting at the pre-school level and usually using the face-to-face method. However, at this time with the diversity of the latest technology and the experience of the effects of the COVID-19 pandemic, a learning method that is more innovative and can be implemented independently is very desirable to be implemented. This also gives a new breath to the teaching and learning of prayer. This paper would like to discuss the development of the Adik-Adik Solat M-Learning Application. The ADDIE methodology is used in the application development cycle process. To identify the level of acceptance of the application as well as to know the characteristics of the application that contribute to the improvement of the learning experience, a survey was conducted on a group of school students. The application of learning methods that emphasize visual, audio, and kinesthetic (VAK) approaches was identified to provide an enhancement to the learning experience. This application has great potential to be commercialized and expanded to other fields in the future.